Effectiveness of cinnamon in the reduction of lipid levels in people with diabetes: a randomized clinical trial - José Cláudio Garcia Lira Neto; Márcio Flávio Moura de Araújo; Antônia Vitória Elayne Carneiro Araújo; Joana Nágila Ribeiro Figueira; Thatiana Araújo Maranhão; Marta Maria Coelho Damasceno (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To evaluate the effectiveness of cinnamon in reducing lipid levels in people with diabetes. Method: Randomized clinical trial of parallel groups, triple-blind, conducted in Basic Health Units in the state of Piauí in 2019. People with Type 2 Diabetes Mellitus, between 18 and 80 years old, using oral antidiabetics, were included, and divided into two groups. The experimental group tested 3g of cinnamon for 90 days. Results: 140 people participated in the study. From these, the experimental group (n= 71) showed a reduction in mean levels of total cholesterol (p= 0.316 | CI 95% -24.9-8.1), LDL (p= 0.024 | CI 95% -29.3 -2.1) and triglycerides (p= 0.969 | 95% CI -28.6-27.5), and increased HDL (p= 0.001 | 95% CI 4.2-10.2). Conclusion: The use of 3g of cinnamon per day, for 90 days, seems to help reduce LDL values and increase HDL levels in patients with diabetes.